Metabolomics reveal alterations in arachidonic acid metabolism in Schistosoma mekongi after exposure to praziquantel - Chienwichai, P; Tipthara, P; Tarning, J; Limpanont, Y; Chusongsang, P; Chusongsang, Y; Adisakwattana, P; Reamtong, O (Public Library of Science, 2021)
Background Mekong schistosomiasis is a parasitic disease caused by the blood-dwelling fluke Schistosoma mekongi. This disease contributes to human morbidity and mortality in the Mekong region, posing a public health threat to people in the area. Currently, praziquantel (PZQ) is the drug of choice for the treatment of Mekong schistosomiasis. However, the molecular mechanisms of PZQ action remain unclear, and Schistosoma PZQ resistance has been reported occasionally. Through this research, we aimed to use a metabolomic approach to identify the potentially altered metabolic pathways in S. mekongi associated with PZQ treatment. Methodology/Principal findings Adult stage S. mekongi were treated with 0, 20, 40, or 100 μg/mL PZQ in vitro. After an hour of exposure to PZQ, schistosome metabolites were extracted and studied with mass spectrometry. The metabolomic data for the treatment groups were analyzed with the XCMS online platform and compared with data for the no treatment group. After low, medium (IC50), and high doses of PZQ, we found changes in 1,007 metabolites, of which phosphatidylserine and anandamide were the major differential metabolites by multivariate and pairwise analysis. In the pathway analysis, arachidonic acid metabolism was found to be altered following PZQ treatment, indicating that this pathway may be affected by the drug and potentially considered as a novel target for anti-schistosomiasis drug development. Conclusions/Significance Our findings suggest that arachidonic acid metabolism is a possible target in the parasiticidal effects of PZQ against S. mekongi. Identifying potential targets of the effective drug PZQ provides an interesting viewpoint for the discovery and development of new agents that could enhance the prevention and treatment of schistosomiasis.